Perlindungan Hukum Terhadap Pekerja yang Melebihi Batas Waktu Kerja di PT. Adi Putra Denpasar - Ngurah Aldi Ramaputra; I Nyoman Putu Budiartha; I Pt Gd Seputra (Fakultas Hukum Universitas Warmadewa, 2020)
Violations of labor problems related to working time that do not comply with this legislation often occur in companies engaged in the industry that is pursuing the target in the production business. One of the companies that want to be researched regarding the implementation of legal protection against workers who work after the deadline of the work, namely PT. Adi Putra Denpasar is a furniture company that is located at Jl. Baypass Ngurah Rai No. 852 Pemogan - Denpasar. Based on the background of the problem can be formulated some of the following problems (1) How is the implementation of legal protection against Labor that works beyond the deadline of work on the company PT. Adi Putra Denpasar? (2) What is the inhibitory factor in the implementation of legal protection against Labor that works beyond the working time limit on the company PT. Adi Putra Denpasar? This type of research in the writing of scientific works is a type of empirical study. In terms of data arranged systematically, then analyzed qualitative so it is expected to get a clear picture of the problem faced. The implementation of legal protection for workers exceeding the time of working hours in PT. Adi Putra Denpasar, has not been fully done in accorsertace with the prevailing provisions, especially against overtime work, hours applied, which is sometimes up to 5 hours, there are also factors The inhibitory found among the other poor performance of workers to work on the production of goods and lack of manpower owned today.